Board Size and Leverage in Indonesian’s Pharmaceutical Companies. The Moderating Role of Profitability - Sanga, Marianus Hendrilensio; Hajanirina, Andrianantenaina (CV. Jala Berkat Abadi, 2023)
This empirical study examines the relationship between board size, leverage, and profitability in the pharmaceutical sector. Using a sample of pharmaceutical companies from 2019 to 2022, the study reveals that board size has a significant positive impact on leverage. Additionally, profitability acts as a moderator in the relationship between board size and leverage. The results indicate a significant negative relationship between board size and leverage when considering profitability, suggesting that larger boards in pharmaceutical companies are associated with lower levels of leverage. These findings contribute to the existing literature on corporate governance and financial performance, highlighting the significance of board size in shaping leverage decisions and influencing profitability. The study suggests that larger boards in the pharmaceutical sector exercise caution in managing debt, leveraging their enhanced monitoring capabilities, diverse expertise, and increased accountability. Policymakers, industry practitioners, and investors can use these insights to make informed decisions regarding board composition, financing strategies, and evaluating the financial performance and risk profiles of pharmaceutical companies.